Optimalisasi media pembelajaran audio visual pada pembelajaran aqidah akhlak di SMP Muhammadiyah Program Khusus Surakarta - Adhytia Gunawan; Hafidz Hafidz (At Turots: Jurnal Pendidikan Islam, 2022)
This research aims to determine and describe the optimization of audio visual-based learning media in the Aqidah Akhlak subject including the supporting and inhibiting factors for optimizing audio-visual-based learning media in Aqidah Akhlak subjects at Special Program School of SMP Muhammadiyah Surakarta. This research uses a qualitative research method with a descriptive approach. The collection techniques in this research are observation, interviews and documents. The validity of the data in this study is source triangulation and technique triangulation. The data analysis techniques in this research are data collection, data reduction, data presentation and conclusion. Sources of data in this research are school principal, Islamic religious education teachers and students in grade seventh. The results of this study indicate that the optimization of audio visual-based learning media in the subject of “Aqidah Akhlak” through YouTube media is used as a learning resource and learning media. It is shown to the screen by projector, then students are invited to pay attention, active and give respond to YouTube videos as a form of active participation in learning activities. The supporting factors for optimizing audio-visual-based learning media in the “Aqidah Akhlak” subject are laid out in adequate facilities and infrastructure for each class. The inhibiting factor for optimizing audio visual-based learning media in the subject of Aqidah Akhlak is the lack of preparation from the teacher himself in preparing the tools used for learning media.